Preliminary design and fast prototyping of an Autonomous Underwater Vehicle propulsion system. (August 2015) - Allotta, Benedetto; Pugi, Luca; Bartolini, Fabio; Ridolfi, Alessandro; Costanzi, Riccardo; Monni, Niccolò; Gelli, Jonathan
The Mechatronics and Dynamic Modelling Laboratory of the Department of Industrial Engineering, University of Florence, as a partner of THESAURUS (Italian acronym for 'TecnicHe per l'Esplorazione Sottomarina Archeologica mediante l'Utilizzo di Robot aUtonomi in Sciami') project, has developed an innovative low-cost, multirole autonomous underwater vehicle, called Tifone. This article deals with the adopted methodologies for the autonomous underwater vehicle design: in particular, the main focus of this study is related to its propulsion system. According to the expected performances and requirements of THESAURUS project, the vehicle has to maintain good autonomy and efficiency (typical features of an autonomous underwater vehicle), with high manoeuvrability and hovering capabilities, which are more common of remotely operated vehicles. Moreover, cooperative underwater exploration and surveillance involve the use of a swarm of vehicles. In particular, the optimization of costs versus benefits is achieved through the design of a fleet of three multirole vehicles. Each autonomous underwater vehicle has five controlled degrees of freedom, thanks to four thrusters and two propellers: in this article, the preliminary design criteria concerning the vehicle and the design and testing of its actuation system are described.